A new learning model of software engineering in vocational education - Dicky Nofriansyah; Ganefri Ganefri; Ridwan Ridwan (International Journal of Evaluation and Research in Education (IJERE), 2020)
This research focused on the development a new learning model in Vocational Education to answer the challenges of this Industrial Revolution 4.0 era. The problem identified was the lack of learning outcomes, especially subjects oriented to software engineering for information systems students in particular and other computer science seen in the phenomenon of the inability of students to produce intelligent systems. From a series of validity, practicality, and effectiveness test results, use content validity with Aiken'V and construct validity with CFA (Confirmatory Factor Analysis) states that the model resulting from this study is stated, valid, practical and effective. This study also produced a new learning model with five syntaxes, namely (1) Define Problem and Design a Plan Project, (2) Interaction with Support System, (3) Create a Project, (4) Keep control and Monitoring Project, (4) Yield and Assessment of Project. And based on the test of the validity of the syntax of this model stated goodness-of-fit or valid.